EFEKTIVITAS MODEL PEMBELAJARAN QUICK ON THE DRAW DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - MULIASIH, IDA; U.S, SUPARDI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2024)
ABSTRAKThis study was motivated by the difficulties of X IPS students of SMA Negeri 10 Tangerang in learning mathematics, especially in understanding the concept of trigonometry. The average math score of students is still less than the Material Completeness Criteria (KKM). In addition, students are less active in participating in the learning process. In group assignments, some students rely on other friends to complete the assigned tasks. Therefore, it is necessary to choose a learning model that suits the conditions in the classroom. This study aims to analyze the effect of Quick on The Draw learning model on the mathematics learning outcomes of students in class X IPS. The Quick on The Draw learning model is a collaborative learning strategy that focuses on increasing student engagement through fun activities that encourage them to answer questions quickly and accurately. The research method used is Classroom Action Research (PTK) with a cycle design, which includes planning, action, observation, and reflection stages. The results showed that the application of the Quick on The Draw model significantly improved students' mathematics learning outcomes, especially in the aspects of speed and accuracy in solving problems. The improvement in learning outcomes was measured through the comparison of scores before and after the implementation of the learning model. Thus, the Quick on The Draw model can be an effective alternative in learning mathematics to improve students' understanding and ability to solve mathematical problems.Penelitian ini dilatarbelakangi oleh kesulitan siswa kelas X IPS SMA Negeri 10 Tangerang dalam pembelajaran matematika khususnya dalam memahami konsep trigonometri. Nilai rata-rata matematika siswa masih kurang dari Kriteria Ketuntasan Materi (KKM). Selain itu siswa kurang aktif dalam mengikuti proses pembelajaran. Dalam tugas kelompok, beberapa siswa mengandalkan teman lainnya untuk menyelesaikan tugas yang diberikan. Karenanya perlu dipilih model pembelajaran yang sesuai dengan kondisi di kelas. Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran Quick on The Draw terhadap hasil belajar matematika siswa kelas X IPS. Model pembelajaran Quick on The Draw adalah strategi pembelajaran kolaboratif yang berfokus pada peningkatan keterlibatan siswa melalui aktivitas menyenangkan yang mendorong mereka untuk menjawab soal secara cepat dan tepat. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan desain siklus, yang meliputi tahap perencanaan, tindakan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa penerapan model Quick on The Draw secara signifikan meningkatkan hasil belajar matematika siswa, terutama pada aspek kecepatan dan ketepatan dalam menyelesaikan soal. Peningkatan hasil belajar tersebut diukur melalui perbandingan nilai sebelum dan sesudah implementasi model pembelajaran. Dengan demikian, model Quick on The Draw dapat menjadi alternatif yang efektif dalam pembelajaran matematika untuk meningkatkan pemahaman dan kemampuan siswa dalam memecahkan masalah matematika.